Rapid biodegradation of atrazine by a novel Paenarthrobacter ureafaciens ZY and its effects on soil native microbial community dynamic - Zhao, Yue; Li, Xin; Li, Yunyang; Bao, Huanyu; Nan, Jun; Xu, Guoren (Frontiers in Microbiology, 2023)
An atrazine-utilizing bacterium, designated as ZY, was isolated from agricultural soil and identified as Paenarthrobacter ureafaciens. The P. ureafaciens ZY demonstrated a significant degradation capacity of atrazine, with the degradation efficiency of 12.5 mg L-1 h-1 in Minimal Salt Medium (MSM) (at pH 7, 30℃, and the atrazine level of 100 mg L-1). The P. ureafaciens ZY contained three atrazine-degrading genes (i.e., trzN, atzB, and atzC) which could metabolize atrazine to form cyanuric acid, and cyanuric acid showed lower biotoxicity than the parent atrazine as predicted by Ecological Structure Activity Relationships (ECOSAR). A laboratory-scale pot experiment was performed to examine the degradation of atrazine by P. ureafaciens ZY incubation and investigate its effects on the native microbial communities. The results exhibited that the P. ureafaciens ZY was conductive to the degradation of atrazine, increased the total soil phospholipid fatty acids (PLFAs) at the atrazine level of 50, 70, and 100 mg kg-1. By using high-throughput sequencing analysis, Frateuria, Dyella, Burkholderia-Caballeronia-Paraburkholderia were considered as the most important indigenous atrazine-degrading microorganisms due to their relative abundances were positively correlated with the atrazine degradation rate. In addition, P. ureafaciens ZY also increased the abundance of atrazine-degrading genus Streptomyces and Bacillus, indicating that there may be a synergic relationship between them in the process of atrazine degradation. Our work provides a new insight between inoculums and native microorganisms on the degradation of atrazine.